Posteroanterior cephalometric norms for an adolescent Kuwaiti population - Al-Azemi, R.; Artun, J. (European journal of orthodontics, 2012)
The aim of the study was to establish posteroanterior (PA) cephalometric norms for adolescent Kuwaitis of an age comparable with the start of comprehensive orthodontic treatment, and to compare these with similar normative data, considering a difference of 2.0 mm or degrees as clinically significant. Digital PA cephalograms of 159 13- to 14-year-old Kuwaitis (81 boys and 78 girls) with untreated ideal occlusions were evaluated. Anatomic landmarks were identified directly on digital computer images and linear and angular measurements were calculated electronically. Mean values (norms), standard deviations, and ranges were calculated for the parameters. Student's t-tests were employed to test for gender differences. The dental norms were clinically similar to those of Ricketts' analysis, but the ranges of the skeletal dental width and relationship measurements were clinically larger. Only the ranges of skeletal symmetry measurements were larger. Regarding the four dental to skeletal relationships, the norms were larger only for the molar to jaw relationship, while the ranges were larger for all. No gender differences were detected after Bonferroni adjustments. The findings suggest clinically significant racial differences in PA cephaolometric norms with minimal gender differences at adolescence. The ranges of the various parameters in adolescent subjects with natural development of an ideal occlusion are considerably larger than those suggested in Ricketts' analysis system.